Frequency of Hyperopia in Children between 5 to 15 Years of Age - Muhammad Usman Arshad, Sohail Zia, Aunaza Maqbool, Rabia Sharif Bhatti, Zamir Iqbal, Yasir Iqbal (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To determine the frequency of hyperopia in children between 5 and 15 years of age. Study Design: Cross sectional study Setting and Duration of Study: Al-Shifa Trust Eye Hospital Rawalpindi between March 2015 to September 2015 Methodology: 150 children between the ages of 5-15 years were included in the study. All children with eye disorders like corneal opacity, retinoblastoma, cataracts, amblyopia, chronic metabolic disorders, and hemoglobinopathies were excluded from the study. The participants were assessed for visual acuity was checked through a LogMAR visual acuity assessment chart for each eye. Those who found to have decreased visual acuity their pin-hole visual acuity was determined and then they got thorough examination by slit lamp biomicroscopy and fundoscopy to rule out causes of decreased vision other than refractive errors. Results: A mean (SD) age of 8.57 (2.52) years with 106 (70.76%) children between 5-10 years and 44 (29.33%) were between 11-15 years of age. Males were predominant in our study with 90/150 (60%) male patients and 60 (40%) female population. The frequency of hyperopia I our study was 93 (62%). Out of 60 female patients, 35 (58.33%) had hyperopia whereas, out of the 90 male patients, 58 (64.4%) patients had hyperopia. Conclusion: We reported that hyperopia is a very frequent refractive disorder found in children. Male are more frequently diagnosed with the disorder between the ages of 5-10 years. Further large-scale cohorts should be conducted to determine the correlating factors that increase the risk of hyperopia and prognosis.